Simulation Study on the Impact Response of Barrels with Different Rifling Profiles during Bullet Engraving. (21st February 2022) - Wei, Zhifang; Cheng, Yangyang; Wang, Zhiwei; Lin, Yanpeng
Abstract : Gun barrel bores are prone to ablative damage and stress concentration under high temperatures, pressures, and dynamic load impacts during bullet engraving, which may result in barrel failure. A dynamic stress analysis during bullet engraving is a prerequisite for barrel life analysis and design. Impact responses during bullet engraving were investigated in this study for rifled barrels with different cross-sectional profiles to improve the match between the dynamic performances of the gun barrel and bullet and effectively extend the barrel service life. First, feature suppression by expression based on a uniform parametrized template was used to perform parametric modeling of a gun barrel with rectangular, trapezoidal, multiarc, and multilateral-arc rifling profiles. Second, theoretical models were constructed considering different rifling structures: a model to calculate the chamber pressure, a model for heat transfer in the barrel during continuous firing, and a model to calculate the friction between a bullet and the barrel wall surface based on shear-slip friction theory. These models were integrated into a simulation, where the ABAQUS (ABAQUS. 6.14.1-4. 2014. DASSAULT SIMULIA.)/Explicit software was used to build a finite element model of the barrel dynamic stress under heat-force-friction coupling during bullet engraving. Finally, the dynamic response stresses were analyzed for bullet engraving into four barrels with different rifling profiles. All four types of barrels developed considerable stress at the junction between the forcing cone and the rifled bone under the same impact load. The stress values of the multiarc and multilateral-arc rifling were far below that for the rectangular and trapezoidal rifling. Thus, the barrels with multiarc and multilateral-arc rifling profiles had a higher impact resistance than the other two barrel types.